2021
DOI: 10.1093/bmb/ldaa044
|View full text |Cite
|
Sign up to set email alerts
|

Osteotomies for avascular necrosis of the femoral head

Abstract: Background In osteonecrosis of the femoral head (ONFH), blood supply is insufficient for the metabolic requirements of the bone. The initial management is conservative, and, in case of failure, surgery is indicated. Osteotomies aim to change the spatial position of the necrotic portion of the femoral head. This systematic review evaluates the effectiveness and safety of osteotomies for ONFH. Source of data The systematic revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 52 publications
0
42
0
Order By: Relevance
“…An osteotomy was a treatment for ONFH by changing the spatial position of the necrotic portion of the femoral head. However, Quaranta et al have reported that approximately one-third of the osteotomies performed in cases of ONFH were converted to THR over 7 years [ 25 ]. The information of nutrient foramina in the fovea capitis femoris mentioned in this study might be used to define the parameters of the patient and improve the outcome of the osteotomy technique.…”
Section: Discussionmentioning
confidence: 99%
“…An osteotomy was a treatment for ONFH by changing the spatial position of the necrotic portion of the femoral head. However, Quaranta et al have reported that approximately one-third of the osteotomies performed in cases of ONFH were converted to THR over 7 years [ 25 ]. The information of nutrient foramina in the fovea capitis femoris mentioned in this study might be used to define the parameters of the patient and improve the outcome of the osteotomy technique.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has a higher complication rate, including the non-union or delayed union of bone at the osteotomy, failure of internal fixation, etc. [ 11 , 15 , 16 ]. Vascularized bone grafts require a high surgical technique, long operation time, extensive trauma, and have highly variable long-term success rates [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, conservative treatment can relieve pain but cannot prevent the process of necrosis, hence the effect is limited. Surgical treatments include core decompression, platelet-rich plasma or bone marrow mesenchymal stem cells, vascularized bone graft, non-vascularized bone graft, and osteotomy [ 9 11 ]. Core decompression is accepted by most orthopedic surgeons as the preferred option for the treatment of ONFH but with wide variation in clinical outcomes [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Femoral head necrosis, a common clinical disease with a high disability rate, is caused by factors such as excessive alcohol consumption and the heavy use of short-term high-dose glucocorticoids (5). In the disease process of femoral head necrosis, the blood supply is not sufficient to maintain the needs of bone metabolism, and the early treatment of the disease is mainly through conservative treatment, and in case of failure of conservative treatment, surgical treatment is required (6). Bukowski et al evaluated 174 patients with AS who underwent total hip arthroplasty and demonstrated an incidence of the posterior hip dislocation of approximately 8% over 20 years (7).…”
Section: Introductionmentioning
confidence: 99%